Concept of Moral Education from the Perspective of Sheikh Muhammad Nawawi Al-Bantani - Yusutria Yusutria; Lidea Francisca; Yuherman Yuherman; Rina Febriana (Yayasan Letiges Konsultan Sosial, 2023)
The function of moral education is moral change that must be accepted in the heart and applied in all patterns of life. Therefore a concept of thought is needed, including the concept of Syekh Muhammad Nawawi Al-Bantani in the Maroqil Ubudiyah Book about moral education. This research is a qualitative research with a literature approach. Primary data sources consist of the Maroqil Ubudiyah Book by Syekh Muhammad Nawawi Al-Bantani and secondary sources that discuss moral education in the form of books and writings by other figures who discuss morals. Data analysis techniques using data reduction, coding, inductive and deductive approaches. The results of the research show that there are 6 concepts of moral education, namely: about the relationship with God; relationship with teachers; the relationship between student and teacher; relationship with parents; relations with lay people; and friendship relations.